Development Impacts of Globalization and Education: Evidence from the Asia-Pacific Countries - Neupane, Pramila; Sapkota, Jeet Bahadur (Crossing the Border: International Journal of Interdisciplinary Studies, 2015)
This article compares globalization, education and development indicators of high-growth and low-growth countries in terms of their GDP per capita in the Asia-Pacific region from 1970 to 2010. Although development is multifaceted, this study mostly considers growth alone as the measure of development. It finds that countries with high level of education at 1970 have achieved high-growth along with rapid globalization over time, and vice versa. Similarly, panel data analysis of selected countries shows that globalization and education significantly enhance the growth. However, despite high level of education and globalization, the Philippines has surprisingly low-growth, high poverty and inequality, which indicates that good policies and institutions should complement globalization and educational base for rapid development. Crossing the Border: International Journal of Interdisciplinary Studies Vol.3(1) 2015: 21-40